FORMULASI SEDIAAN BLUSH ON DARI SARI BUAH STROBERI (Fragaria vesca L) SEBAGAI PERONA PIPI - Sianipar, Artha Yuliana; Nurbaya, Siti; Adiansyah, Adiansyah; Sitanggang, Eva Priasanti (UNIVERSITAS SARI MUTIARA INDONESIA, 2020)
Colorisone of the determining factors for the quality of cosmetics. The use of synthetic colors in blus her can cause irritation on facial skin. Because of that, wetried to make a blush preparation using natural dyes, namely strawberries (Fragariavesca L). The purpose of this study was to make blushusing natural dyesfromstrawberries (Fragariavesca L). The juice is obtaineddirectly using a juicer machine, then heated in a waterbath /Waterbath to obtain a thick juice of strawberry fruit (Fragariavesca L) with a concentration of 15; 25; 35%. The resultsshowedthatthepreparationwashomogeneous, remainedstable, did not cause irritation, wassafe for the skin because thep Hofthepreparation was still in the normal skin phrange of 4.5-6.5, and was quiteliked by the respondents. The conclusion of this study shows that strawberry juice (Fragariavesca L) canbeused as a blush (blush), but the resulting colorisless visible.